Blockchain Technology as a Security Enhancement Framework for Internet of Things: A Comprehensive Analysis - Gokul Balaguruswamy Naidu (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The exponential growth of Internet of Things (IoT) devices has introduced significant security challenges that traditional cybersecurity measures struggle to address effectively. This research presents a comprehensive analysis of blockchain technology’s integration with IoT systems as a solution to enhance security, privacy, and trust in connected device ecosystems. Through systematic evaluation of implementation architectures, security frameworks, and real-world applications, this study demonstrates how blockchain’s inherent characteristics of decentralization, immutability, and cryptographic security can effectively address critical IoT vulnerabilities. The research examines specific applications across supply chain management, healthcare systems, and smart city infrastructure, providing quantitative and qualitative evidence of security improvements. While acknowledging challenges in scalability, energy consumption, and regulatory compliance, the study presents innovative solutions and future directions, including AI integration and privacy-enhancing technologies. The findings indicate that blockchain-IoT integration significantly improves data integrity, device authentication, and access control mechanisms, reducing security incidents by up to 60% in implemented cases. This research contributes to the growing body of knowledge on secure IoT architectures and provides practical insights for organizations considering blockchain implementation in their IoT security frameworks.